Gambaran empati pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi angkatan 2011 - Runtuwarow, Stardia; Pasiak, Taufiq F.; Ticoalu, Shane H.R. (eBiomedik, 2017)
Abstract: Empathy is a potential psychological motivator for helping others in distress. Empathy can be defined as the ability to feel or imagine another person’s emotional experience. The ability to empathize is an important part of social and emotional development, affecting an individual’s behavior toward others and the quality of social relationships. This was a descriptive quantitative study using cross sectional design. Empathy scale questionnaires were filled in by 76 students of the Faculty of Medicine, University of Sam Ratulangi Manado who were active as co-assisants at Prof. Dr. R. D. Kandou Hospital. The results showed that the majority had high empathy, with an average overall score of empathy of female co-assistants was higher than of male co-assistants. Conclusion: Empathy of students of Faculty of Medicine, University of Sam Ratulangi batch 2011 was categorized as high.Keywords: emphaty, medical students Abstrak:. Empati adalah motivator potensi psikologis untuk membantu orang lain yang dalam kesulitan. Empati dapat didefinisikan sebagai kemampuan untuk merasakan atau membayangkan pengalaman emosional orang lain. Kemampuan untuk berempati merupakan bagian penting dari perkembangan sosial dan emosional, memengaruhi perilaku individu terhadap orang lain dan kualitas hubungan sosial. Jenis penelitian ini ialah deskriptif kuantitatif dengan menggunakan desain potong lintang. Angket skala empati diisi oleh 76 mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado yang sedang aktif menjalankan tugas sebagai co-assisant di RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian menunjukkan hasil empati mayoritas tinggi, dengan rerata keseluruhan skor empati perempuan lebih tinggi dibandingkan dari laki-laki. Simpulan: Gambaran empati mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Angkatan 2011 tergolong tinggi.Kata kunci: empati, mahasiswa Kedokteran